IBN QAYYIM AL-JAUZIAH DAN PENDAPATNYA TENTANG TRADISI KALAM - Ulin Na'mah (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2015)
A worriness about the mix of ilm al-kalam with ilm al-Mantiq of Aristoteles, which is considered inconsistent, have prompted several Muslim thinkers like Ibn Taimiyah and Ibn Qayyim Al-Jauziah to ban the available ilm al-kalam at that time. They both believed that, in ilm al-Mantiq of Aristoteles, there is no qiyas aula or an effort of humanizing God and, therefore, it will result in not recognizing God as creator of universe (because universe exists by himself). Thus, the tradition of Â ilm al-Mantiq have made someone to be kufr. Meanwhile, the ulama of kalam have tended to also used Aristotelesâ€™ framework of thinking in building their arguments. At the end, ulama of kalam have also trapped in kufr.Keywords: Tradisi Ilmu Kalam, Mutakallimun, Ilmu Mantiq dan Kekufuran